Satellite Earth Observation as a Catalyst for Sustainable Business Development: Economic and Managerial Perspectives - Kostikov, Eva; Iqbal, Zahid; Bushra, Mehmood (Publishing House of Wroclaw University of Economics and Business, 2025)
This paper examines how satellite-based Earth Observation (EO) data can support smarter business decisions, sustainability, and risk reduction. Through semi-structured interviews with seven professionals from sectors such as agriculture, logistics, and urban planning, the study identifies four themes: current EO use, strategic benefits, barriers to adoption, and future potential. The results showed that EO helps with crop health monitoring, route optimisation, biodiversity tracking, and ESG reporting. The challenges include data complexity, high costs, and organisational resistance. The study recommends better integration tools, training, and partnerships. EO is positioned not just as a technical tool, but as a driver of resilient, data-informed, and sustainable business strategies.
Quote as: Kostikov, E., Iqbal, Z., & Bushra, M. (2025). Satellite Earth Observation as a Catalyst for Sustainable Business Development: Economic and Managerial Perspectives. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 151-169). Publishing House of Wroclaw University of Economics and Business.
Keywords: Earth Observation; satellite data; business decision making; strategic intelligence; sustainability reporting; remote sensing; digital transformation